Ascorbic acid is involved in melatonin-induced salinity tolerance of maize (Zea mays L.) by regulating antioxidant and photosynthetic capacities - Zhu, M; Guo, T; Liu, Y B; Xiao, R; Yu, T; Huang, J X; Du, W L; Zhong, X M; Song, B; Li, F H (Photosynthetica, 2024)
Melatonin (MT), an indole compound, can boost plant growth under abiotic stress conditions. This experiment aims to elucidate the synergistic effect of MT and ascorbic acid (AsA) in mitigating salinity stress by assessing the photosynthetic and antioxidant capacity of the maize inbred lines H123 and W961. The results indicated that exogenous MT and AsA significantly improved photosynthetic efficiency and biomass of maize under salinity stress. Additionally, exogenous MT and AsA also improved antioxidant enzyme activities, promoted regeneration of AsA and GSH, decreased reactive oxygen species contents, suppressed Na+ accumulation, and improved the K+/Na+ ratio of maize seedlings. Additionally, the AsA inhibitor lycorine decreased the endogenous content of AsA and eliminated the positive effects of MT, while the MT inhibitor p-chlorophenyl alanine (CPA) reduced the endogenous content of MT, which could not eliminate the promoting effects of AsA. The results suggested that AsA may act as a downstream signal involved in the regulatory effects of MT on maize under salinity stress.
Keywords: Photosynthesis; Zea mays; salinity stress; reaktivní formy kyslíku; Sodium; salinita; semenáček; melatonin; Ascorbic Acid; maize; kukuřice setá; Salinity; Antioxidants; Reactive Oxygen Species; ionic homeostasis; antioxidancia; kyselina askorbová; AsA–GSH cycle; Salt Tolerance; ascorbic acid; Seedlings; sodík; tolerance k soli; fotosyntéza; Melatonin